Ragam Deiksis Pesona dan Waktu dalam Cerpen Smokol Karya Nukila Akmal - Nurul Kholiza; Moh Jailani (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
Deixis is a field of pragmatic study that discusses the relationship between language structures. and where the language is spoken. The use of the term "deixis" is being observed or noticed in this context. Most often seen in daily conversation is in the form of spoken language. Found in character dialogue in literary works such as films. The study entitled "Variations of Charm Deixis and Time Deixis in the Short Story Smokol by Nukila Akmal" examines the use of various charm deixis and time deixis by Nukila Akmal. Person and time deixis are part of the variety of deixis studied in this research. Researchers use analytical methods in the form of pragmatics with qualitative techniques to analyze the data that has been collected. The data used in this research include fragments of speech from short story conversations, both words and phrases that contain deixis, including: charm deixis and time deixis. The reading-note method of capturing data, recognizing, categorizing, analyzing, formulating and presenting data are the stages of analysis in this research. Data analysis illustrates that a short story written by Nukila Akmal with the title Smokol has a deixis of charm and time.